2023
DOI: 10.3390/diagnostics13162688
|View full text |Cite
|
Sign up to set email alerts
|

Elevated UTI Biomarkers in Symptomatic Patients with Urine Microbial Densities of 10,000 CFU/mL Indicate a Lower Threshold for Diagnosing UTIs

Abstract: The literature lacks consensus on the minimum microbial density required for diagnosing urinary tract infections (UTIs). This study categorized the microbial densities of urine specimens from symptomatic UTI patients aged ≥ 60 years and correlated them with detected levels of the immune response biomarkers neutrophil gelatinase-associated lipocalin (NGAL), interleukin-8 (IL-8), and interleukin-1-beta (IL-1β). The objective was to identify the microbial densities associated with significant elevation of these b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“… 22 Our recent data on midstream voided specimens support the clinical validity of the ≥ 10,000 CFU/mL threshold. 23 We have also demonstrated that microbial densities reported as cells/mL by M-PCR are equivalent to CFU/mL reported by SUC. 24 …”
Section: Introductionsupporting
confidence: 72%
“… 22 Our recent data on midstream voided specimens support the clinical validity of the ≥ 10,000 CFU/mL threshold. 23 We have also demonstrated that microbial densities reported as cells/mL by M-PCR are equivalent to CFU/mL reported by SUC. 24 …”
Section: Introductionsupporting
confidence: 72%
“…Six studies were classified as having high risk of bias ( 36 , 38 40 , 43 , 49 ). Seven remaining studies had unclear risk of bias ( 37 , 45 , 51 , 52 , 54 56 ). Details on the rating of each risk of bias are shown in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…We compared the biomarker levels among specimens with no microorganisms detected by either M-PCR or SUC, with specimens that were M-PCR-positive/SUC-negative, M-PCR-negative/SUC-positive, and M-PCR-positive/SUC-positive. We evaluated two thresholds of microbe positivity: 100 000 cells/ml or CFUs/ml, which is traditionally considered diagnostically significant for UTIs in the USA, and 10 000 cells/ml or CFUs/ml, which has been suggested as more clinically relevant in recent clinical reviews and guidelines and in our own studies [20] , [22] , [23] . Since M-PCR has previously been demonstrated to be superior at detecting non– E. coli or polymicrobial infections [5] , [6] , [7] , [8] , [9] , we further examined cases where E. coli was detected, non– E. coli organisms were detected, and two or more microorganisms were detected in the same specimen (polymicrobial).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were performed according to two microbial density thresholds of positivity (10 000 cells/ml by M-PCR or colony forming units (CFUs)/ml by SUC, and 100 000 cells/ml or CFUs/ml). The 100 000 cells/ml or CFUs/ml threshold is traditionally considered diagnostically significant in the USA; however, clinical reviews and guidelines in addition to our data [20] , [21] have suggested a lower microbial density threshold of 10 000 cells/ml or CFUs/ml is clinically relevant [22] , [23] . Participant demographics and ICD-10-CM diagnostic code breakdown were described by summary statistics (eg, mean and standard deviation for continuous variables such as age and count, and percentage for categorical variables such as sex and ICD-10-CM codes).…”
Section: Methodsmentioning
confidence: 99%